The Role of Social Capital in the Experiences of Hispanic Women Engineering Majors. Issue 2 (19th July 2013) - Martin, Julie P.; Simmons, Denise R.; Yu, Shirley L.
Abstract Background Women and minorities remain significantly underrepresented in the undergraduate engineering disciplines despite decades‐long recruitment and retention efforts. As United States demographics shift and the nation continues to recognize the value of workplace diversity, engineering education stakeholders continue to seek ways to increase participation of women and minority students. Purpose Our research examines the following question: For Hispanic women whose parents have limited educational attainment, what available sources of potential social capital do they identify, and by what means do they access and activate these resources in their decisions to select and persist in engineering as a college major? We hope to provide insights for United States institutions that serve Hispanic students, as well as those seeking to diversify their student body. Design/method Utilizing Lin's network theory of social capital as a framework, we employed semi‐structured interviews in a multiple case study research methodology, taking a constructivist epistemological view. Results Three major findings are that (1) lack of available family social capital was supplemented mostly by school personnel; (2) delayed recognition or identification of available resources slowed access and activation of resources, leading to difficult university transitions; and (3) if accessed and activated, peer groups and institutional support systems provided sources of social capital. Conclusions Even single instances or weak ties can be effective in bridging gaps in engineering‐related social capital. Facilitating opportunities for students to develop sustained social capital may have potential to attract and retain underrepresented students in engineering.